Pencegahan Korosi pada Beton dalam Masa Perawatan dengan Cat Anti-korosi berbasis Bituminous - Pinta Astuti; Ridha Kautsari Fahma (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2022)
Concrete is a versatile material that is widely used in the construction industry nowadays. However, reinforced concrete has durability issues due to corrosion, which can reduce the structure's service life. Corrosion occurs as a result of high water vapor levels in the environment, as well as extreme air changes accompanied by chloride ion intrusion at the marine environment. As a result, corrosion prevention is required to control the corrosion potential of steel reinforcement in newly fabricated reinforced concrete structures. In this study, corrosion prevention used bituminous-based anti-corrosion paint on the surface of steel reinforcement before fabricating the specimens. The corrosion test specimen is a 15cmx15cmx15cm cube mortar with two embedded steel bars placed 3cm and 5cm from the specimen's upper surface to simulate the thickness of the concrete cover. There are two types of reinforcement treatment variations, with or without anti-corrosion coating at the steel bar surface, each variation consist of three specimens. This study also tested the mechanical properties of concrete, such as flow table, compressive strength, split tensile, density, and shrinkage. The half-cell potential method was used to observe the probability of corrosion for 28 days during the concrete curing period using the water immersion method. According to the corrosion probability test results, the steel reinforcement using bituminous-based anti-corrosion paint had a lower corrosion potential value than the specimen that did not receive coating. Furthermore, specimens with a concrete cover of 5 cm have a lower corrosion potential value than specimens with a concrete cover of 3 cm